Analisis Faktor-Faktor Yang Mempengaruhi Struktur Modal: Studi Kasus Pada Sektor Industri Asuransi - Dwi Urip Wardoyo; Adventia Dita Andani (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: The aim of this research is to determine the influence of the capital structure of the insurance industry listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period which is influenced by profitability, leverage, asset structure and company size. Methodology/approach: This research uses quantitative methods and uses purposive sampling techniques to collect observation data from a sample of 17 companies so that this research obtained 68 samples. Furthermore, data analysis in this research involves descriptive statistical analysis and panel data regression analysis using Eviews version 12 software. Findings: The findings of this research indicate that profitability and leverage are able to have a positive influence on the company's capital structure. Meanwhile, the asset structure and company size cannot have an influence on the capital structure of the insurance industry listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. Practical implications: Practically this research contributes to investors and potential investors to always be wise in considering factors that affect the company’s capital structure so that it can make the right investment. Contributions are also given to the company to pay attention to variables that may risk affecting the capital structure so that the company does not suffer losses. Originality/value: Integrating four independent variables with a special focus on the insurance industry listed on the Indonesia Stock Exchange for the 2019-2022 period